ANALISA TATA LETAK INDUSTRI PENGALENGAN BUAH NENAS DI BATU JAWA TIMUR - Endang Rusdiana; Sakunda Anggarini (BUANA SAINS, 2010)
All fruits, in the post harvest were easily to damage. Pineapples were also easily to damage so it need the method to maintain its quality. Canning was the process that food or fruits were proceed and than packed in a sealed container and sterilized to kill microbial decomposers and pathogens that were harmful and detrimental to human. The aimed of this study were to analyze the plant layout and facilities at PT. Berjaya Sekawanindo Batu. The results showed that needed for improvements and restructuring the layout of the plant because the material flow pattern and interrelationships of activities were still not an appropriated places and materials. The accumulation of material flow and material handling and facilities spacing were still maximum. The recommendations for new layout design has ability for minimum crossing. This layout would helped to reduce material handling costs, considering the frequency of work flow and increase flexibility to change in demand